Effect of perioperative blood transfusion on the long-term survival of patients undergoing esophagectomy for esophageal cancer: a systematic review and meta-analysis. Issue 4 (18th December 2017) - Boshier, P R; Ziff, C; Adam, M E; Fehervari, M; Markar, S R; Hanna, G B
SUMMARY: Perioperative blood transfusion has been linked to poorer long-term survival in patients undergoing esophagectomy, presumably due to its potential immunomodulatory effects. This review aims to summarize existing evidence relating to the influence of blood transfusion on long-term survival following esophagectomy for esophageal cancer. A systematic literature search (up to February 2017) was conducted for studies reporting the effects of perioperative blood transfusion on survival following esophagectomy for esophageal cancer. Meta-analysis was used to summate survival outcomes. Twenty observational studies met the criteria for inclusion. Eighteen of these studies compared the outcomes of patients who received allogenic blood transfusion to patients who did not receive this intervention. Meta-analysis of outcomes revealed that allogenic blood transfusion significantly reduced long-term survival (HR = 1.49; 95% CI 1.26 to 1.76; P  < 0.001). There appeared to be a dose-related response with patients who received ≥3 units of blood having lower long-term survival compared to patient who received between 0 and 2 units (HR = 1.59; 95% CI 1.31 to 1.93; P  < 0.001). Two studies comparing patients who received allogenic versus autologous blood transfusion showed superior survival in the latter group. Factors associated with the requirement for perioperative blood transfusion included: intraoperative blood loss; preoperative hemoglobin; operative approach; operative time, and; presences of advanced disease. These findings indicate that perioperative blood transfusion is associated with significantly worse long-term survival in patients undergoing esophagectomy for esophageal cancer. Autologous donation of blood, meticulous intraoperative hemostasis, and avoidance of unnecessary transfusions may prevent additional deaths attributed to this intervention.